A Review of Sustainability Model in Manufacturing Organization Towards IR4.0 in Malaysia - Ghazali, Mohamad Fazali; Saad, Rohaizah (ExcelingTech, 2020)
This paper reviews a sustainability model in manufacturing organization towards IR4.0 focusing on three main factors, which are continuous improvement, organizational culture and organizational sustainability. This review is based on the several general criterias, i.e. total quality management, strategy, development model, business performance measurement, teamwork, leadership and continuous improvement practices. Then, the summary of these reviews is discussed. The results show that the sustainability model which should occur there is an improvement in terms of knowledge of tool management skills, methodology, as well as standards and network security in order to be able to take on IR 4.0. Thus, the presence of sustainability models with diverse approaches and strengths can help future researchers to achieve work practices and organizational strategies leading towards IR4.0